Modular vaccine packaging increases packing efficiency. Issue 27 (17th June 2015) - Norman, Bryan A.; Rajgopal, Jayant; Lim, Jung; Gorham, Katrin; Haidari, Leila; Brown, Shawn T.; Lee, Bruce Y.
Abstract: Background: Within a typical vaccine supply chain, vaccines are packaged into individual cylindrical vials (each containing one or more doses) that are bundled together in rectangular "inner packs" for transport via even larger groupings such as cold boxes and vaccine carriers. The variability of vaccine inner pack and vial size may hinder efficient vaccine distribution because it constrains packing of cold boxes and vaccine carriers to quantities that are often inappropriate or suboptimal in the context of country-specific vaccination guidelines. Methods: We developed in Microsoft Excel (Microsoft Corp., Redmond, WA) a spreadsheet model that evaluated the impact of different packing schemes for the Benin routine regimen plus the introduction of the Rotarix vaccine. Specifically, we used the model to compare the current packing scheme to that of a proposed modular packing scheme. Results: Conventional packing of a Dometic RCW25 that aims to maximize fully-immunized children (FICs) results in 123 FICs and a packing efficiency of 81.93% compared to a maximum of 155 FICs and 94.1% efficiency for an alternative modular packaging system. Conclusions: Our analysis suggests that modular packaging systems could offer significant advantages over conventional vaccine packaging systems with respect to space efficiency and potential FICs, when they are stored in standard vaccine carrying devices. This allows for more vaccines to be stored within the same volume while also simplifying the procedures used by field workers to pack storage devices. Ultimately, modular packaging systems could be a simple way to help increase vaccine coverage worldwide.